Advances in cognitive psychology - Wyższa Szkoła Finansów i Zarządzania w Warszawie (Published on behalf of the University of Finance and Management in Warsaw by Vizja Press & IT Ltd, 2005)
Advances in Cognitive Psychology is a web-based journal devoted to the scientific study of the human mind. The journal's broad focus encompasses the behavioral, cognitive, and brain sciences. The journal publishes empirical studies, theoretical papers, and critical reviews.
Keywords: Cognitive psychology : Periodicals; Neuropsychology : Periodicals; Psychology, Experimental : Periodicals; Cognitive psychology; Neuropsychology; Psychology, Experimental; Cognition; Psychologie; cognition; psychology; Cognition; Psychology